A record of magmatic differentiation in plutonic xenoliths from Santorini (Greece) - Whitley, Sean; Halama, Ralf; Gertisser, Ralf; Hansteen, Thor H.; Frische, Matthias; Vennemann, Torsten (Volcanica, 2024)
Plutonic xenoliths from volcanic arcs provide unique insights into transcrustal magmatic systems in subduction zone settings. At Santorini volcano in the Central Aegean Volcanic Arc (Greece), plutonic xenoliths occur throughout a sequence of lavas and pyroclastic rocks erupted within the last ~360 ka. They are mineralogically variable, ranging from troctolites to olivine gabbros, gabbros, gabbronorites, and diorites. Thermobarometric calculations based on mineral and melt inclusion compositions indicate equilibration over a range of temperatures (1100 to 750 °C) at shallow to mid-crustal depths (P <400 MPa), but there is no evidence for crystallisation at lower crustal depths. Oxygen isotope data of mineral separates and calculated δ18O melt values are in line with extensive closed-system fractional crystallisation at magmatic temperatures, without a requirement for extensive assimilation of the subvolcanic continental basement. The xenolith minerals compositionally overlap with phenocrysts from the volcanic rocks, but they also contain evidence for the presence of highly evolved melt compositions in the form of melt inclusions with extremely silica-rich compositions (up to 82 wt.% SiO2) and high enrichments of incompatible trace elements coupled with increasing negative Eu anomalies in clinopyroxenes. Since these characteristics correlate systematically with differentiation indices and rock type, they are interpreted to reflect melt evolution via fractional crystallisation as the dominant differentiation process with no significant role of reactive porous flow. These observations highlight that trapped melt fractions can influence mineral compositional variations in the plutonic xenoliths, and in turn the mineral compositions demonstrate a melt compositional variability not preserved in the volcanic rock record.